Dividend Policy on Non-Financial Sector: The Impact of Ownership Structure with Moderating Growth Opportunity - Juliani, Meily; Candra, Rudi; Valentine, Vivy (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
In this study, the collected data using a quantitative method of the annual reports on non-financial companies Indonesia Stock Exchange (IDX) that distribute dividends in 5 years, namely 2018-2022. This study aims to determine the impact of dividend policy on ownership structure with moderating growth opportunities. The specific ownership structures in this study are institutional ownership, state ownership, family ownership, and foreign ownership. The testing method in this study is the panel regression method, with the best model testing in this analysis being FEM. The results of this test show that only family ownership and return on assets significantly impact dividend policy. This result means that the distribution of dividends received is also higher, along with increasing family ownership and ROA. This research will provide an overview to potential investors in choosing a company as a consideration for investment implementation.